(untitled) (PALIMPSEST / ПАЛИМПСЕСТ, 2020)
The article will examine how the authors Arkady and Boris Strugatsky created their own picture of the Middle Ages in the story “Hard to be a God” (1964). The events in the novel unfold on another planet with an unknown name, in the city Arkanar, the capital of the Arkanar kingdom. This planet is a part of the so-called World of Noon in literary pieces by Strugatsky Brothers and represents a special world that can be compared with the transitional stage between late feudalism and the Renaissance in the history of the Earth. Keywords: Russian literature of the XX century, science fiction, A. and B. Strugatsky, Middle Ages.